Peran Kepala Madrasah Wanita Dalam Pengelolaan Penerimaan Siswa Baru Di Mi Maarif Brajan Banjararum Kalibawang Kulon Progo - Salim, Ahmad (Literasi: Jurnal Ilmu Pendidikan, 2013)
Among the principal’s role is to manage the educational institution in getting the number of new students in accordance with the standards that have been done, so it can run educational prosess normally. This study was conducted to find out the role of Principle MI Maarif Brajan Banjar Arum Kalibawang Kulon Progo in getting new students. This study becomes very important due to the Principle MI Maarif is a woman who has a limited step compared with men, but since her leadership the number of new students was increasing. The results showed that the priciple MI Maarif may act as a manager, leader and supervisor and therefore contributes to the satisfaction of internal and external environment prospective student input. Some supporting factors such as the qualification and competence of the Principle MI Maarif Brajan are qualified and religius societie’s sect is same as MI Maarif Brajan Banjararum Kalibawang Kulon Progo.  Keyword: woman principle’s role, management new students